2021
DOI: 10.3390/su131910577
|View full text |Cite
|
Sign up to set email alerts
|

Hiring Disable People to Avoid Staff Turnover and Enhance Sustainability of Production

Abstract: Companies struggle with maintaining staff turnover at a low and sustainable level. Hiring a new employee means costs for the company, such as recruitment, medical examinations, and training, etc. In addition, new employees must learn to perform their tasks properly and quickly, which can take up to several months. Disabled employees change jobs less frequently due to the fact that it is difficult for them to find a new one. For employers, such an employee, if they have the same skills as a fully functional emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Moreover, the turnover rate is higher among them in comparison to able-bodied employees (Chi and Qu 2004;Kim 2015). On the other hand, based on other studies, employees with disabilities are motivated, loyal, and responsible; their productivity level is almost equal to their non-disabled colleagues (Chajduga and Ingaldi 2021;Chao et al 2018;Jammaers et al 2016). A study by Katz et al (2015) concluded that employees with high-functioning autism spectrum disorders (HFASD) are honest people and are highly responsible since none of them were required to quit their jobs due to behavioural and professional matters during the 9-month study in Israel.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the turnover rate is higher among them in comparison to able-bodied employees (Chi and Qu 2004;Kim 2015). On the other hand, based on other studies, employees with disabilities are motivated, loyal, and responsible; their productivity level is almost equal to their non-disabled colleagues (Chajduga and Ingaldi 2021;Chao et al 2018;Jammaers et al 2016). A study by Katz et al (2015) concluded that employees with high-functioning autism spectrum disorders (HFASD) are honest people and are highly responsible since none of them were required to quit their jobs due to behavioural and professional matters during the 9-month study in Israel.…”
Section: Introductionmentioning
confidence: 95%
“…Productivity and job performance among employees with impairments/disabilities are research questions that have not been answered yet in psychology, human development, sociology, social work, and so on. Other disability-related issues such as policies, rights, quality of life, job satisfaction, the unemployment rate of people with disabilities (PWDs) and caregivers, and employers' attitudes toward their willingness to hire PWDs were discussed in many studies (Alkaabi 2022;Anderson et al 2021;Bastas and Altinay 2019;Butterworth et al 2020;Chajduga and Ingaldi 2021;Choi et al 2018;King and Waghorn 2018;Ochrach et al 2022;Pihlajamäki et al 2020;Rotaru et al 2021;Werner and Hochman 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An important part of sustainability implementation is to deal with the practices that preserve biodiversity, eliminate social inequalities, and prevent the unsustainable use of limited resources [2]. Various authors focus on economic sustainability [3][4][5], environmental sustainability [6][7][8][9], and social sustainability [10][11][12][13]. However, for a better 2030 and beyond, the United Nations (UN) double-clicked on the three elements of sustainability, defined it in 17 factors, and named them the Sustainable Development Goals (hereafter SDGs) by 2015.…”
Section: Introductionmentioning
confidence: 99%